Model Optimasi Konsolidasi Hot Dan Cold Maintenance Untuk Peningkatan Keandalan Operasional Pltmg Ambon Peaker Pada Sistem Kelistrikan Terisolasi - Arung, Arnold; Suef, Mokh (Lembaga Teewan Journal Solutions, 2026)
The Ambon Peaker Gas Engine Power Plant, with an installed capacity of 39.12 MW, plays a critical role in maintaining the reliability of the Maluku power system, which operates as an isolated system. As a peaker plant, the unit is required to maintain high operational readiness in responding to load fluctuations and system disturbances. However, frequent start-stop operation accelerates component degradation, increases maintenance requirements, and raises the risk of equipment failure if maintenance activities are not properly structured. Maintenance activities in gas engine power plants are generally carried out through Hot Maintenance and Cold Maintenance. Hot Maintenance minimizes operational disruption but is limited in terms of component accessibility, inspection depth, and occupational safety. In contrast, Cold Maintenance enables more comprehensive inspection and repair but requires unit shutdown and affects plant availability during the outage period. This research applies a descriptive-analytical case study approach through maintenance activity identification, classification based on operating conditions and outage requirements, model parameter development, consolidation scoring, scenario analysis, and expert validation through Focus Group Discussion (FGD). The proposed model classifies maintenance activities into Hot Maintenance, Cold Maintenance, Consolidated Planned Outage, and FGD Review. The results show that the proposed consolidation optimization model reduces cold outage frequency from 18 events to 3 events per year. Total outage duration decreases from 198 hours to 162.36 hours. The total cost of the consolidation model is estimated at IDR 1,353.6 million, resulting in cost savings of IDR 1,425.4 million or 51.3% compared with the baseline condition. In terms of reliability, the model improves EAF from 81.50% to 82.48%, reduces FOR from 8.50% to 6.70%, increases MTBF from 840 hours to 926.5 hours, and reduces MTTR from 22 hours to 19.74 hours. The contribution of this study is an applicable maintenance consolidation optimization model for peaker power plants operating in isolated power systems. The model can support structured maintenance work packaging, reduce repetitive maintenance activities, optimize resource utilization, improve planned outage effectiveness, and strengthen maintenance planning for the Ambon Peaker Gas Engine Power Plant.